Psychometric properties of the Brazilian version of the Pain Catastrophizing Scale for acute low back pain - Renata Antunes Lopes; Rosângela Corrêa Dias; Bárbara Zille de Queiroz; Nayza Maciel de Britto Rosa; Leani de Souza Máximo Pereira; João Marcos Domingues Dias; Lívia de Castro Magalhães (Arquivos de Neuro-Psiquiatria)
Measurement instruments of pain catastrophizing for middle-aged and elderly individuals are needed to understand its impact on low back pain. The goals were to cross-culturally adapt the Pain Catastrophizing Scale, assess the construct validity through Rasch analysis, and verify reliability and convergent validity of pain catastrophizing with psychosocial factors. 131 individuals aged 55 years and older with acute low back pain were interviewed . The intra-rater reliability was Kp = 0.80 and interrater Kp = 0.75. The Rasch analysis found adequate reliability coefficients (0.95 for items and 0.90 for individuals ). The separation index for the elderly was 2.95 and 4.59 items. Of the 13 items, one did not fit the model, which was justified in the sample evaluated. The pain catastrophizing correlated with most psychosocial factors. The instrument proved to be clinically useful. Subsequent studies should carry out the same analysis in different populations.